Irregular warfare strategy and considerations - Milton, Arnold; Berkovski, Walt; Gray, Colin S. (Nova Science Publishers, 2012)
At present, America s enemies are of an irregular character. These irregular enemies necessarily wage war in modes that are largely unconventional. Joint operations concepts describe how the joint force is expected to conduct joint operations within a military campaign in the future. They identify the broad military capabilities necessary to achieve the ends envisioned by the concept. Since the original version of the Irregular Warfare Joint Operating Concept was approved in September 2007, the understanding of irregular warfare has continued to evolve. This book explores how the joint forces must operate to counter irregular threats and to guide force development, material and non-material capability development, and experimentation when directed by the President or Secretary of Defense, to prevent, deter, disrupt and defeat non-state actors, as well as state actors who pose irregular threats.